2017
DOI: 10.1136/bmjgh-2017-000376
|View full text |Cite
|
Sign up to set email alerts
|

Collecting data for global surgical indicators: a collaborative approach in the Pacific Region

Abstract: In 2015, the Lancet Commission on Global Surgery (LCoGS) recommended six surgical metrics to enable countries to measure their surgical and anaesthesia care delivery. These indicators have subsequently been accepted by the World Bank for inclusion in the World Development Indicators. With support from the Royal Australasian College of Surgeons and the Pacific Islands Surgical Association, 14 South Pacific countries collaborated to collect the first four of six LCoGS indicators. Thirteen countries collected all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 24 publications
2
74
1
Order By: Relevance
“…However, using methodologies that measure local travel time to facilities more precisely, other studies have found considerably lower proportions of the population within 2h of a facility. The current methods of estimating travel time to facilities may not reflect on‐the‐ground reality. Geographic Information System methods do not account for lack of, or breakdowns in, transport, the impact of road traffic, seasonal effects on travel speeds, or referral patterns between hospitals providing appropriate care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, using methodologies that measure local travel time to facilities more precisely, other studies have found considerably lower proportions of the population within 2h of a facility. The current methods of estimating travel time to facilities may not reflect on‐the‐ground reality. Geographic Information System methods do not account for lack of, or breakdowns in, transport, the impact of road traffic, seasonal effects on travel speeds, or referral patterns between hospitals providing appropriate care.…”
Section: Discussionmentioning
confidence: 99%
“…The data collection interval was 2010–2016, and publication of the Commission report in 2015 and other global initiatives to improve access to safe affordable surgical care in that year were an incentive to collect data. Indeed, data collection is ongoing (frequently driven by professional societies and researchers rather than governments and multilateral organizations) and, in some instances, new data have been published since data collection for this study ended. New data are not always nationally representative, and have increased availability only marginally; challenges to comparability and utility also remain.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a widespread shortfall in the number of procedures performed across the region, accepting the global surgical volume target of 5000 per 100 000, but ranging from 433 to 5061 per 100 000, national surgeons are now operating all across the South Pacific. The region, apart from Timor Leste, is no longer reliant on expatriate surgeons either to provide essential services, or to be faculty for surgical MMed training.…”
Section: Impact Of Surgical Training Programmesmentioning
confidence: 99%
“…The Lancet Commission on Global Surgery recommended provision of 20 specialist surgeons, anaesthetists and obstetricians (SAOs) per 100 000 population. Currently SAO provider ratios in the Pacific range from 0·9 to 14 per 100 000, with the most populous nations of Papua New Guinea (PNG) and Timor Leste at the bottom of the range ( Table ). Wherever access to SAOs is limited, one option, albeit a short‐term solution, is to increase the number of trained providers through task‐sharing or task delegation: training other health workers to provide essential services, as in some parts of sub‐Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to assess institutional capacity and access to surgical services is vital for global health planning. The Lancet Commission bellwether procedures have been used to map 2-hour access to emergency and essential surgical care globally [82][83][84][85] . This helps to identify areas to prioritise global health funding and efforts to help reach the target of 80% coverage of essential surgical and anaesthetic care per country by 2030 81 .…”
Section: Gastroschisis As a Bellwether Conditionmentioning
confidence: 99%